Perspectives on Entangled Nuclear Particle Pairs Generation and Manipulation in Quantum Communication and Cryptography Systems - Octavian Dănilă; Paul E. Sterian; Andreea Rodica Sterian (Advances in High Energy Physics)
Entanglement between two quantum elements is a phenomenon which presents a broad application spectrum, being used largely in quantum cryptography schemes and in physical characterisation of the universe. Commonly known entangled states have been obtained with photons and electrons, but other quantum elements such as quarks, leptons, and neutrinos have shown their informational potential. In this paper, we present the perspective of exploiting the phenomenon of entanglement that appears in nuclear particle interactions as a resource for quantum key distribution protocols.